Sex matters: impact on pathogenesis, presentation and treatment of inflammatory bowel disease - Goodman, Wendy A.; Erkkila, Ian P.; Pizarro, Theresa T. (Nature reviews. Gastroenterology & hepatology, 2020)
Inflammatory bowel disease (IBD), as do most chronic inflammatory disorders, displays unique features and confers different risk factors in male and female patients. Importantly, sex-based differences in IBD exist for epidemiological incidence and prevalence among different age groups, with men and women developing distinct clinical symptoms and disparity in severity of disease. In addition, the presentation of comorbidities in IBD displays strong sex differences. Notably, particular issues exclusive to women’s health, including pregnancy and childbirth, require specific considerations in female patients with IBD of childbearing age that can have a substantial influence on clinical outcomes. This Review summarizes the latest findings regarding sex-based differences in the epidemiology, clinical course, comorbidities and response to current therapies in patients with IBD. Importantly, the latest basic science discoveries in this area of investigation are evaluated to provide insight into potential mechanisms underlying the influence of sex on disease pathogenesis, as well as to design more personalized and efficacious care, in patients with IBD. Inflammatory bowel disease (IBD) has different manifestations and associated risk factors between the sexes. This Review explores the sex-based differences in presentation and management of IBD, as well as insights into sex-based differences in pathogenesis and underlying mechanisms inferred from basic research. Key points Epidemiological studies have shown a greater predominance and severity of Crohn’s disease in women than in men, but a greater predominance and severity of ulcerative colitis in men than in women. Epidemiological studies have also demonstrated that colorectal cancer is more common among men than among women with chronic ulcerative colitis with a high degree of inflammation. Female sex hormones, including oral contraceptives, influence the immune system and contribute to the exacerbation of IBD symptoms in women. Female patients with IBD who wish to become pregnant are advised to wait until clinical remission. The incidence of extraintestinal manifestations and comorbidities in patients with IBD frequently shows differences between men and women. Two experimental mouse models of Crohn’s disease (SAMP1/YitFc and Tnf ΔARE/+ strains) recapitulate female sex bias and represent promising tools for future mechanistic studies underlying sex-based differences in IBD pathogenesis.